019 Development and validation of a novel pressure-only intra-coronary index of coronary stenosis severity. (16th May 2012) - Sen, S; Escaned, J; Malik, I; Mikhail, G; Foale, R; Mila, R; Tarkin, J; Petraco, R; Broyd, C; Jabbour, R; Sethi, A; Baker, C; et al.
Abstract : Background: Assessment of stenosis severity with fractional flow reserve (FFR) requires that coronary resistance is stable and minimised. This is usually achieved by administration of pharmacological agents such as adenosine, which adds to the cost of the procedure and cannot be administered to all patients. In this study we determine (1) if there is a time when resistance is naturally minimised at rest and (2) assess the diagnostic efficiency, compared to FFR, of a new pressure-derived adenosine-free index of stenosis severity over that time. Methods: 157 stenoses were assessed. In part 1 (39 stenoses), intracoronary pressure and flow-velocity were measured distal to the stenosis; in part 2 (118 stenoses), intracoronary pressure alone was measured. Measurements were made at baseline and under pharmacological vasodilatation with adenosine. Results: Wave intensity analysis identified a wave-free period where intracoronary resistance at rest is similar in variability and magnitude (coefficient of variation: 0.08±0.06 and 284±147 mm Hg.s/m) to those during FFR (coefficient of variation: 0.08±0.06 and 302±315 mm Hg.s/m, p=NS for both). The resting distal to proximal pressure ratio during this period, the instantaneous wave-Free Ratio (iFR), correlated closely with FFR (r=0.9, p<0.001) with excellent diagnostic efficiency (receiver operating characteristic area under curve of 93%, at FFR<0.8), specificity, sensitivity, negative and positive predictive values of 91%, 85%, 85% and 91%, respectively. Conclusion: Intra-coronary resistance is naturally constant and minimised during a diastolic wave-free period. The instantaneous wave-Free Ratio calculated over this period produces a drug-free index of stenosis severity comparable to FFR. Adoption of instantaneous wave-Free Ratio would enable the benefits of physiologically guided angioplasty to be applicable to a larger patient population.